Prospective Teachers’ Metacognitive Awareness in Remote Learning: Analytical Study Viewed from Cognitive Style and Gender - Muhammad Asy'ari; Cleci T. Werner da Rosa (International Journal of Essential Competencies in Education, 2022)
Cognitive regulation related to the learning independence is a problem that often appears in remote learning. It’s related to metacognition awareness that claimed could facilitate learners in understanding how to learn and regulate the learning process to solve the new problem encountered. The current study aimed to investigate the prospective science teachers’ (PST) metacognitive awareness in remote learning based on field-dependent and field-independent cognitive styles, and gender. Quantitative research with a survey method involving 100 PST was carried out in this study. The PST metacognitive awareness was collected using the Metacognition Awareness Inventory (MAI) instrument, while PST cognitive style was determined using the Group Embedded Figure Test (GEFT) instrument, which was empirically declared valid and reliable. The research data were analyzed using the independent sample t-test, and the Mann-Whitney test after the data distribution test was carried out using the Kolmogorov-Smirnov test. Based on gender differences, PST metacognitive awareness was not significantly different (p>0.05), while based on cognitive style, PST metacognitive awareness was significantly different (p<0.05) on indicators of procedural knowledge and conditional knowledge. In addition, PST metacognitive awareness was significantly different on indicators of procedural knowledge, conditional knowledge, planning, monitoring, debugging, and evaluation based on a review of cognitive styles and gender differences.